Neurological manifestations of dengue infection. - Solomon, T; Dung, N; Vaughn, D; Kneen, R; Thao, LT; Raengsakulrach, B; Loan, H; Day, N; Farrar, J; Myint, K; Warrell, M; James, W; et al. (2000)
BACKGROUND: Severe forms of dengue, the most important arboviral infection of man, are associated with haemorrhagic disease and a generalised vascular leak syndrome. The importance of dengue as a cause of neurological disease is uncertain. METHODS: During 1995, all patients with suspected CNS infections admitted to a referral hospital in southern Vietnam were investigated by culture, PCR, and antibody measurement in serum and CSF for dengue and other viruses. FINDINGS: Of 378 patients, 16 (4.2%) were infected with dengue viruses, compared with four (1.4%) of 286 hospital controls (odds ratio [95% CI] 3.1 [1.7-5.8]). Five additional dengue positive patients with CNS abnormalities were studied subsequently. No other cause of CNS infection was identified. Seven infections were primary dengue, 13 secondary, and one was not classified. Ten patients had dengue viruses isolated or detected by PCR, and three had dengue antibody in the CSF. 12 of the 21 had no characteristic features of dengue on admission. The most frequent neurological manifestations were reduced consciousness and convulsions. Nine patients had encephalitis. No patient died, but six had neurological sequelae at discharge. Phylogenetic analysis of the four DEN-2 strains isolated mapped them with a DEN-2 strain isolated from a patient with dengue haemorrhagic fever, and with other strains previously isolated in southern Vietnam. INTERPRETATION: In dengue endemic areas patients with encephalitis and encephalopathy should be investigated for this infection, whether or not they have other features of the disease.